A Study on Amitav Ghosh’S Novel the Hungry Tide: Exploring love, identity, and survival in the treacherous Sundarbans (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Hungry Tide is the sixth novel by Indian-born author,Amitav Ghosh. It tells a very contemporary story of adventure and unlikelylove, identity and history, set one of the most fascinating regions on theearth. Off the easternmost coast of India, in the Bay of Bengal, lies theimmense labyrinth of tiny islands known as the Sundarbans. For settlers here, lifeis extremely precarious. Attacks by deadly tigers are common. Unrest andeviction are constant threats. Without warning, at any time, tidal floods riseand surge over the land, leaving devastation in their wake. In this place ofvengeful beauty, the lives of three people from different worlds collide.